Investigation of rotor-stator interaction and flow unsteadiness in a low specific speed centrifugal pump - Zhang, Ning (Strojniški vestnik, 2016)
Instantaneous flow dynamics induced by rotor-stator interaction are detrimental to the stable operation of centrifugal pumps. In this study, unsteady rotor-stator interaction and flow structures within a low specific-speed centrifugal pump are analysed using the Large Eddy Simulation (LES) method. For that purpose, pressure pulsations and the evolution processes of vortical structures are combined to investigate rotor-stator interaction in order to clarify the inherent correlation between pressure amplitude and vorticity distribution. The results show that distinct peaks at blade passing frequency ( f BPF ) are closely associated with the positions of the monitoring point due to rotor-stator interaction. An unsteady vortical structure at the near tongue region is related to the relative position of the impeller with respect to the tongue, and the upstream effect of the volute tongue significantly affects the vorticity distribution on the blade pressure side. Rotor-stator interaction is dominated by vortex shedding in the wake of the blade trailing edge and their impingement on the volute tongue with subsequent cutting and distortion. Moreover, the high-pressure amplitude is generated with the corresponding high vorticity magnitude observed as well. Therefore, it is confirmed that pressure amplitude is significantly associated with the corresponding vorticity magnitude.
Keywords: centrifugalna črpalka; interakcije med rotorjem in statorjem; nestacionaren tok; simulacija velikih vrtincev; tlačni impulzi; vrtinčna struktura